The skills of defibrillation practice and certified life‐support training in the healthcare providers in Turkey. Issue 12 (14th November 2021) - Derinoz‐Guleryuz, Oksan; Uysal‐Yazici, Mutlu; Udurgucu, Muhammed; Karacan, Candemir; Akça, Halise; Ongun, Ebru Atike; Ekinci, Faruk; Duman, Murat; Akça‐Çaglar, Ayla; Vatansever, Goksel; Bilen, Sevcan; Uysalol, Metin; et al.
Abstract: Aim of the study: Successful cardiopulmonary resuscitation and early defibrillation are critical in survival after in‐ or out‐of‐hospital cardiopulmonary arrest. The scope of this multi‐centre study is to (a) assess skills of paediatric healthcare providers (HCPs) concerning two domains: (1) recognising rhythm abnormalities and (2) the use of defibrillator devices, and (b) to evaluate the impact of certified basic‐life‐support (BLS) and advanced‐life‐support (ALS) training to offer solutions for quality of improvement in several paediatric emergency cares and intensive care settings of Turkey. Methods: This cross‐sectional and multi‐centre survey study included several paediatric emergency care and intensive care settings from different regions of Turkey. Results: A total of 716 HCPs participated in the study (physicians: 69.4%, healthcare staff: 30.6%). The median age was 29 (27‐33) years. Certified BLS‐ALS training was received in 61% (n = 303/497) of the physicians and 45.2% (n = 99/219) of the non‐physician healthcare staff ( P  < .001). The length of professional experience had favourable outcome towards an increased self‐confidence in the physicians ( P  < .01, P  < .001). Both physicians and non‐physician healthcare staff improved their theoretical knowledge in the practice of synchronised cardioversion defibrillation ( P  < .001, P  < .001). Non‐certified healthcare providers were less likely to manage the initial doses of synchronised cardioversion and defibrillation: the correct responses remained at 32.5% and 9.2% for synchronised cardioversion and 44.8% and 16.7% for defibrillation in the physicians and healthcare staff, respectively. The indications for defibrillation were correctly answered in the physicians who had acquired a certificate of BLS‐ALS training ( P  = .047, P  = .003). Conclusions: The professional experience is significant in the correct use of a defibrillator and related procedures. Given the importance of early defibrillation in survival, the importance and proper use of defibrillators should be emphasised in Certified BLS‐ALS programmes. Certified BLS‐ALS programmes increase the level of knowledge and self‐confidence towards synchronised cardioversion‐defibrillation procedures.